A CFD based approach for determination of ammonia concentration profile and flux from poultry houses with natural ventilation (2016)
The understanding of concentration and emissions distribution of gases such as ammonia (NH3) in agricultural installations is of growing importance due to its effect on health and productivity of animals and workers. The objective of this study was to use validated Computational Fluid Dynamics (CFD) model as a tool to predict NH3 concentration distribution and mass fluxes in a non-insulated broiler chicken installation with natural ventilation, typically found in subtropical and tropical countries. Results from this study indicated that simulation with CFD can be used to predict NH3 concentration distribution and mass flux inside similar installations with incident winds from different directions of entrance at the lateral opening of the installation. The most direct application of the proposed model would be to help improving the existing buildings and also to help in the conception of new ones, and may also apply the model to help in the development of NH3 emission inventories